Implementation of Child Friendly Pesantren Program - Albert, Albert; Sesmiarni, Zulfani; Husni, Arman (Jurnal Pendidikan Indonesia, 2024)
This research discusses the correlation between the results of socialization of child-friendly pesantren program by the ministry of religion and the ministry of women’s empowerment and protection on the program implementation in pesantrens in Padangpanjg City, West Sumatra. The purpose of the research was to obtain information about the correlation between the results of socialization on the implementation of the child-friendly pesantren program. The hypothesis in this study is that there is a correlation between the results of socialization and the on the implementation of child-friendly pesantren programs in Pesantrens in Padangpanjang City. The research method is descriptive method.The technique used in this research is proportionate stratified random sampling technique.The results showed that the proposed hypothesis was accepted that there was a significant correlation between the results of socialization on the implementation of the child-friendly pesantren program with he correlation coefficient calculation known that r hitung is 0,660 wheres r table with significant degree 5% for N = 62 and df = N-2 = 62 - 2 = 60 is 0,254. Thereby r hitung ≥ rtabel or 0,660 > 0,254, thereby Ha is accepted.